"It's more fun in the Philippines": Resemiotizing and commodifying the local in tourism discourse. (December 2017) - Valdez, Paolo Nino M.; Tupas, Ruanni; Carol Tan, Neslie
Abstract: Since globalization is characterized by mobility of resources, the tourism industry is considered as one potential area for those interested in language and globalization. While tourism can be attributed to the growing capitalist dream of exploration, it is replete with asymmetrical hierarchies that are motivated by consumption, exploitation and commodification. This paper examines the Philippines' campaign, ' It ' s more fun in the Philippines ', a supposedly grassroots initiative which sought individual contributions from the public such as memes that could help promote the Philippines. The paper finds that the linguistic and multimodal resources of contributions chosen for the campaign showcase a pattern of resemiotization : the use of generic expressions and concepts to present the 'local'. Whereas the original intention of the grassroots initiative was to solicit a diversity of ways to present the Philippines, we find that the official choice of campaign resources has affirmed resemiotization as a linguistic and semiotic strategy of commodification – the repackaging of the local as a construct possessing material value. While much has been said about the use of the local for the global consumer, the paper describes through the lens of language use in the context of globalization how an avowedly ground up and empowering initiative eventually becomes enmeshed in the normalizing processes of globalization.